Safe Generation and Direct Use of Chlorine Azide in Flow Chemistry: 1,2-Azidochlorination of Olefins and Access to Triazoles - Leforestier, Baptiste; Vögtle, Markus (Synlett, 2016)
A safe, fast procedure for the formation of chlorine azide and its trapping by 1,2-addition reaction on olefins is described. ClN3 was generated in situ from NaN3 and NaOCl in the presence of acetic acid, hosted in an organic phase to avoid decomposition and exposed to various alkenes. A copper-catalyzed click reaction then afforded triazoles from the resulting addition products. Telescoping of both reactions was enabled by an in-line workup and subsequent liquid–liquid separation.
Keywords: chlorine azide; addition; alkene; flow chemistry; telescoping; 1,4-disubstituted 1,2,3-triazole